On collaboration : personal, educational and societal arenas - Andriessen, Jerry; Baker, Michael, 1960- (Educational Research E-Books Online, Collection 2020, ISBN: 9789004407381., 2020)
"On Collaboration: Personal, Educational and Societal Arenas provides an elaborated analysis of what it means to collaborate, particularly in educational contexts. It thereby adopts a mixed-genre approach, following L. Vygotsky, who maintained that, for example, the works of Shakespeare and of Dostoyevsky had as much to teach us about the human psyche as laboratory studies and field observations. The authors draw on results of scientific research, particularly on collaborative learning and work, as well as on autobiographical narrative and analysis of works of art. In addition, they broaden the scientific perspective on collaboration from purely educational perspectives by including personal, artistic, and societal contexts. By exploiting benefits of different styles and genres (expository, narrative, fictional, argumentative) this text intends to lead readers towards further reflection on collaboration in their own lives, and towards deeper understanding of the complexity and misconceptions of collaboration, including its societal relevance"--